2014
DOI: 10.1136/bmjopen-2013-004179
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to guidelines in the use of biological agents to treat psoriasis in Brazil

Abstract: ObjectiveIn São Paolo, Brazil, patients can appeal to the courts, registering law suits against the government claiming the need for biological agents for treatment of psoriasis. If the lawsuits are successful, which is usually the case, the government then pays for the biologic agent. The extent to which the management of such patients, after gaining access to government payment for their biologic agents, adheres to authoritative guidelines, is uncertain.MethodsWe identified patients through records of the St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…Also in Brazil, a cross‐sectional study including 203 patients that had, through lawsuits filed against the state of São Paulo in the period 2004–2010, gained access to biologics for treatment of psoriasis with adalimumab (6.9%), efalizumab (21.2%), etanercept (17.2%) and infliximab (54.7%), evaluated the standards and adherence of management of psoriasis common to major international guidelines . Their results showed that access to biologics is largely through prescriptions by private practitioners, and that only 16.7% of patients met the guidelines before beginning biologic treatment with topical and non‐biological systemic therapy.…”
Section: Resultsmentioning
confidence: 99%
“…Also in Brazil, a cross‐sectional study including 203 patients that had, through lawsuits filed against the state of São Paulo in the period 2004–2010, gained access to biologics for treatment of psoriasis with adalimumab (6.9%), efalizumab (21.2%), etanercept (17.2%) and infliximab (54.7%), evaluated the standards and adherence of management of psoriasis common to major international guidelines . Their results showed that access to biologics is largely through prescriptions by private practitioners, and that only 16.7% of patients met the guidelines before beginning biologic treatment with topical and non‐biological systemic therapy.…”
Section: Resultsmentioning
confidence: 99%
“…Interventions, including effective drug monitoring and regulations, and encouraging rational use, have been well described in studies that have addressed, among others, the translation of knowledge through a brief political and deliberative discourse (de Araujo et al; Fulone et al). In addition, aspects related to the challenges and impact of control policies were addressed in the study by Ranabhat et al Some authors have shown that when there is a lack of effective drug control and monitoring, either due to wrong selection of essential drugs for reimbursement or lack of demand-side measures (Godman et al, 2014;Fulone et al, 2016;Osorio-De-Castro et al, 2018) or lack of adherence of official guidelines, health and expenditures (Silveira et al, 2014;De Camargo et al, 2016) may be compromised.…”
Section: Editorial On the Research Topicmentioning
confidence: 99%
“…In addition, aspects related to the challenges and impact of control policies were addressed in the study by Ranabhat et al. Some authors have shown that when there is a lack of effective drug control and monitoring, either due to wrong selection of essential drugs for reimbursement or lack of demand-side measures ( Godman et al., 2014 ; Fulone et al., 2016 ; Osorio-De-Castro et al., 2018 ) or lack of adherence of official guidelines, health and expenditures ( Silveira et al., 2014 ; De Camargo et al., 2016 ) may be compromised.…”
mentioning
confidence: 99%
“…12 Evidence, however, continues to accumulate to support that the full potential of these magic bullets has not been realized because patients continue to be considerably undertreated globally. [13][14][15] In a series of US surveys performed by the National Psoriasis Foundation from 2003 to 2011, the proportion of patients with moderate to severe psoriasis who remain untreated has plateaued at approximately 30%. 13 Moreover, more than 20% of patients with moderate to severe psoriasis continue to be treated with topical therapies alone and more than 50% of patients are dissatisfied with their treatment.…”
mentioning
confidence: 99%
“…14 In Brazil, similar discrepancies exist between actual clinical practice and the recommendations included in the relevant guidelines, thus negatively influencing optimal patient care. 15 The reasons for these inconsistencies include low awareness of therapy availability; lack of understanding of therapy use or monitoring; concerns over adverse effects; lack of effectiveness; and the inability to secure appropriate national insurance coverage or payment for the recommended biological therapies. This finding begs the question as to whether the much-heralded new era for disease management from 2003 has actually been fulfilled.…”
mentioning
confidence: 99%